A 'medical' diagnosis in the trauma clinic. (24th May 2013) - Hussain, Kosar; AlNajjar, Firas Jafar Kareem; Ahmad, Mohammad Javad; Hussain, Sahar
Abstract : A previously healthy 27-year-old Nepalese man presented with a history of direct low-impact direct trauma to the left leg. An x-ray was performed in a private hospital and he was referred to our emergency department for the management of a possible foreign body in the left leg. X-ray of the left leg showed a single, small, 'cigar-shaped' calcified lesion in the posterior aspect of the left leg. There was an inconsistency between the injury and x-ray finding. As the patient originated from a region endemic in Taenia solium, a clinical suspicion for cysticercosis was raised. The patient was then sent for a skeletal survey which subsequently confirmed our diagnosis.